2014
DOI: 10.1159/000358218
|View full text |Cite
|
Sign up to set email alerts
|

Combined Screening for Serum Anti-Nuclear and Anti-Aquaporin-4 Antibodies Improves Diagnostic Accuracy for Distinguishing Neuromyelitis Optica from Multiple Sclerosis

Abstract: Background/Aims: Neuromyelitis optica spectrum disorders (NMOSDs) and multiple sclerosis (MS) are distinct clinical entities but are poorly distinguished by serum markers, including serum anti-aquaporin-4 (AQP4-Ab). We examined if testing for serum anti-nuclear antibodies (ANAs) and AQP4-Ab improved diagnostic sensitivity for NMOSDs. Methods: Chinese patients with NMOSDs (n = 74) or MS (n = 49) were screened for serum ANAs (all patients) and AQP4-Ab (58/74 NMOSDs and 45/49 MS patients). The NMOSDs group includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
1
9
1
Order By: Relevance
“…Antiphospholipid antibodies are not exclusive of APS and may be found less steadily and/or in low titers in infections ( 21 ), in CVT ( 5 ), and in several autoimmune diseases including MS ( 22 25 ) and NMO spectrum disorders (NMOSD) ( 26 ). Reactivity for aPL and other autoantibodies has been reported more frequently in NMOSD compared to MS ( 26 , 27 ), confirming the already known higher occurrence of aPL in “neuromyelitic” type of MS ( 28 ).…”
Section: Specificity and Similarities Of Thrombotic And Demyelinatingsupporting
confidence: 75%
“…Antiphospholipid antibodies are not exclusive of APS and may be found less steadily and/or in low titers in infections ( 21 ), in CVT ( 5 ), and in several autoimmune diseases including MS ( 22 25 ) and NMO spectrum disorders (NMOSD) ( 26 ). Reactivity for aPL and other autoantibodies has been reported more frequently in NMOSD compared to MS ( 26 , 27 ), confirming the already known higher occurrence of aPL in “neuromyelitic” type of MS ( 28 ).…”
Section: Specificity and Similarities Of Thrombotic And Demyelinatingsupporting
confidence: 75%
“…the association of ANA with AQP4 Ab seropositivity increases the sensitivity of NMO diagnosis without reducing the specificity [161].…”
Section: -Autoantibodies Without Diseasesmentioning
confidence: 98%
“…Antibodies such as anti-phospholipid and anti-cardiolipin [73,154,155], antinuclear antibody (ANA) [73,156,157], anti-SSA and SSB [73,158], perinuclear anti-neutrophil cytoplasmic antibodies (pANCA) [73,159], rib nucleoprotein (RNP) [160], single-and double-stranded DNA antibodies, anti-centromere antibodies, thyroid peroxidase antibodies, anti-Scl70 antibodies, anti-histone antibodies, lactoferrin-specific pANCA, pANCA of unknown specificity, anti-smooth muscle antibodies and rheumatoid factor, and antimitochondrial antibodies [73,122] have been variably reported without any evidence of clinical disease. ANA and Anti-SSA are more common among this list [64,161]. It is now argued that…”
Section: -Autoantibodies Without Diseasesmentioning
confidence: 99%
“…NMOSD is a more severe disorder characterized by optic neuritis, longitudinally extensive myelitis and autoantibody positivity against the water channel aquaporin-4. It has been demonstrated that reactivity for different autoantibodies, including antinuclear and antiphospholipid antibodies (aPL), is more frequent in NMOSD compared to MS [1,2].Iong and colleagues [1] have confirmed a significantly higher positive rate for anticardiolipin antibodies (aCL) in NMOSD (45.7 %) compared to MS (5.6 %). We found a similar aCL positivity (5 %) in MS patients, although the overall aPL positive rate increased up to 60 % when the reactivity for more aPL was evaluated [3].…”
mentioning
confidence: 99%
“…NMOSD is a more severe disorder characterized by optic neuritis, longitudinally extensive myelitis and autoantibody positivity against the water channel aquaporin-4. It has been demonstrated that reactivity for different autoantibodies, including antinuclear and antiphospholipid antibodies (aPL), is more frequent in NMOSD compared to MS [1,2].…”
mentioning
confidence: 99%